Profiling of differentially expressed genes in human uterine leiomyomas. Issue 1 (1st January 2005) - Lee, E.-J.; Kong, G.; Lee, S.-H.; Rho, S. B.; Park, C.-S.; Kim, B.-G.; Bae, D.-S.; Kavanagh, J. J.; Lee, J.-H.
Abstract : Uterine leiomyomas are very common benign tumors resulting in clinically serious gynecological problems in women of reproductive age. Approximately, 1% of leiomyosarcoma was reported to arise in a preexisting leiomyoma. However, the molecular basis of these tumors is poorly understood. To understand the molecular changes during leiomyoma development, we profiled differentially expressed genes in ten paired leiomyoma and normal myometrial tissues using cDNA microarray chip analysis. We identified 67 genes (27 overexpressed and 40 underexpressed) which were scored as differentially expressed at least twofold in at least eight of ten patients. Eighteen of 67 genes have been already reported to be differentially expressed without their established functions in uterine leiomyoma and others have never been reported. Subsequently, the relative expression levels of representative genes from identified 67 genes were confirmed by reverse-transcriptase polymerase chain reaction and immunohistochemistry and were found to be consistent with the microarray data. This study could provide a new insight into the understanding of leiomyoma and leiomyosarcoma.